Impact of Growing Rod Surgery for Early-Onset Scoliosis on Cervical Sagittal Alignment - Shuhei Ito; Satoshi Suzuki; Yohei Takahashi; Masahiro Ozaki; Osahiko Tsuji; Narihito Nagoshi; Mitsuru Yagi; Morio Matsumoto; Masaya Nakamura; Kota Watanabe (Spine Surgery and Related Research)
Study Design: Single-institution retrospective study. Objective: To assess the impact of growing rods (GRs) on postoperative cervical sagittal alignment in patients with early-onset scoliosis (EOS). Summary of Background Data: Cervical sagittal malalignment is associated with neck and cervical spine dysfunction. The impact of surgery for adolescent idiopathic scoliosis on postoperative changes in cervical spine alignment has been reported by studies. Nevertheless, research on sagittal and spinopelvic parameters in patients with EOS is limited. Methods: In this study, 28 patients who underwent GR and were followed up until final fusion or bone maturity were included. Standing whole-spine radiographs obtained before GR, after the initial GR surgery, and at the final follow-up were utilized to measure the radiographic parameters. Patients with one or more of the previously reported poor prognostic factors were included in the cervical malalignment (CM) group (n=13), and those with none of the factors were included in the non-CM group (n=15) at the final follow-up, which was followed by correlation analysis and multivariate logistic regression analysis. Results: No significant change in sagittal alignment between preoperative and final follow-up measurements was found. Pearson correlation analysis revealed a significant positive correlation between the change in the C2-7 angle and T1 slope (T1S) or thoracic kyphosis and a negative correlation between the change in the C2-7 angle and T1S minus C2-7 angle (T1S−CL). The percentage of patients in the CM group increased from 25% preoperatively to 46% at the final follow-up but without significant change. The CM group had significantly smaller preoperative C2-7 angles and lumbar lordosis (LL) and larger T1S−CL and pelvic incidence minus LL (PI−LL) values than the non-CM group. Conclusion: Smaller preoperative C2-7 angles and larger T1S−CL values were identified as risk factors for CM. Postoperative CM is more likely to occur in patients with reduced compensatory function to maintain preoperative cervical kyphosis.